Sosialisasi Sertifikasi Halal Bagi Pelaku Usaha Kecil Dan Mikro Di Kecamatan Marawola Kabupaten Sigi Biromaru Sulawesi Tengah - Pratiwi, Indri (-, 2025)
The variety of products circulating in Indonesia is extensive. Each product requires a halal label to facilitate Muslim consumers in identifying and choosing halal-certified items. Therefore, halal certification is essential to ensure the halal status of products for the public, particularly for Muslims. Halal certification is defined as the formal recognition of a product's halal status, issued by the Halal Product Assurance Organizing Agency (BPJPH) based on a written fatwa from the Indonesian Ulema Council (MUI). UIN Datokarama Palu plays a role in accelerating the halal certification process by implementing a self-declare scheme. This community service activity aimed to provide information on how to apply for halal certification, particularly for micro and small business actors, through the self-declare method based on the business owner's statement. The activity was conducted through material delivery sessions and interactive question-and-answer discussions. The results were analyzed using a descriptive qualitative approach through field observation. The socialization was found to be effective in reaching business actors and enhancing their basic understanding of halal certification. Although the level of participation was high, several challenges remained, particularly in terms of technical procedures and digital literacy.